Supporting New Academics’ Use of Student Centred Strategies in Traditional University Teaching - Plush, Sally; Kehrwald, Benjamin (Journal of University Teaching and Learning Practice, 2014)
Despite the perceived advantages of student centred learning (SCL) in higher education, novice teaching academics’ attempts to implement such approaches may be thwarted by a lack of experience with teaching in general and with SCL in particular, difficulties locating suitable practical advice on SCL, and the demands of early career academic workloads. This article seeks to provide practical assistance to teaching academics seeking to implement SCL into traditional teaching environments. It synthesizes current literature to provide an overview of 3 broad SCL strategies: inquiry learning, concept checks and just-in-time teaching. Key considerations for implementing each of these strategies are identified and the authors discuss four observations about the implementation of SCL, in context.